A history of the UN human rights programme and secretariat - Ramcharan, B. G. (International studies in human rights ;, 2020)
"This volumes constitutes a valuable and unique history of the United Nations human rights programme and its secretariat. It offers interpretations of the history of the programme and its secretariat against the background of historical currents such as the Cold War, colonialism and decolonisation, and covers the seminal period during which the programme moved decisively towards human rights fact-finding and the denunciation of violations of human rights, which took place in the latter part of the 1970s and the 1980s. The author was a central player in this period, having served as the Special Assistant to three Directors of the Human Rights Division, and so provides historical materials that only he is aware of, having been at the heart of the action. He also provides snapshots of United Nations human rights leaders from the beginning of the United Nations, all of whom he knew personally, and writes about the contributions of NGOs and NGO leaders who served the cause of human rights with fortitude and determination"--